Efisiensi Pengungkapan Modal Intelektual dalam Perusahaan - Inanda Shinta Anugrahani (Universitas Jember, 2021)
The business dynamics of the 21st century have led to sudden changes. This sudden shift manifested itself as a shift from industry-based business to technology and knowledge. The purpose of this research is to understand various aspects that support the practice of intellectual capital disclosure, intellectual capital measurement methods, barriers and challenges to intellectual capital disclosure, as well as guidelines that can be used for intellectual capital disclosure. This research uses the library method. The type of information used in this research is secondary information sourced from previous literature. The results of the study indicate that the practice of disclosing intellectual capital is very important. This is because intellectual capital is important and relevant information that must be known by stakeholders. Intellectual capital is taken into account in the decision-making process, which can help companies manage assets more optimally. Basically, the guidelines regarding intellectual capital in Indonesia are implicitly stated in PSAK 19. Keywords: Efficiency, Disclosure, Intellectual Capital